Natural Products as Topoisomerase II Poisons: Effects of Thymoquinone on DNA Cleavage Mediated by Human Topoisomerase IIα - Ashley, Rachel E. (American Chemical Society, 2014)
[Image: see text] The seeds of Nigella sativa (often referred to as black seed) have long been utilized as a medicinal herb in Middle Eastern, Northern African, and Indian cultures. Historically, black seed has been used to treat a variety of illnesses associated with inflammation. More recent studies have found that it induces apoptosis and displays anticancer activity in animal and cellular models. The major bioactive compound of black seed is thymoquinone, which shares structural features with 1,4-benzoquinone and other covalent topoisomerase II poisons. Because a number of anticancer drugs target type II topoisomerases, we determined the effects of thymoquinone and a series of related quinones on human topoisomerase IIα. Thymoquinone enhanced enzyme-mediated DNA cleavage ∼5-fold, which is similar to the increase seen with the anticancer drug etoposide. In order to enhance cleavage, compounds had to have at least two positions available for acylation. Furthermore, activity was decreased by the inclusion of electron-donating groups or bulky substituents. As predicted for a covalent topoisomerase II poison, the activity of thymoquinone (and related compounds) was abrogated by the addition of a reducing agent. Also, thymoquinone inhibited topoisomerase IIα activity when incubated with the enzyme prior to the addition of DNA. Cleavage complexes formed in the presence of the compound were stable for at least 8 h. Lastly, black seed extract and black seed oil both increased levels of enzyme-mediated DNA cleavage, suggesting that thymoquinone is active even in more complex herbal formulations. These findings indicate that thymoquinone can be added to the growing list of dietary and medicinal natural products with activity against human type II topoisomerases.